2021
DOI: 10.1182/bloodadvances.2021005292
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-cell therapy for secondary CNS DLBCL

Abstract: Management of secondary central nervous system involvement (SCNSL) in relapsed or refractory aggressive B-cell lymphomas remains an area of unmet medical need. We report a single center retrospective analysis of seven adult patients with SCNSL who underwent CAR-T therapy for their refractory disease and describe safety of whole brain radiation as a bridging therapy. Six patients (85.7%) achieved a complete response at D+28, while 1 patient had progressive disease. The median progression free survival was 83 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“… 43 46 One important exception might be CAR T cells with emerging data showing feasibility and efficacy, although the majority of patients still need effective bridging therapies. 38 , 47 49 Of the five patients in this study who received CAR T cells, two had CNS involvement and responded but one relapsed within 3 months. CAR T cells might play an important role in this setting given recent data showing superiority of certain CAR T cell products over AHCT in patients with high-risk relapsed or refractory systemic DLBCL or HGBL.…”
Section: Discussionmentioning
confidence: 93%
“… 43 46 One important exception might be CAR T cells with emerging data showing feasibility and efficacy, although the majority of patients still need effective bridging therapies. 38 , 47 49 Of the five patients in this study who received CAR T cells, two had CNS involvement and responded but one relapsed within 3 months. CAR T cells might play an important role in this setting given recent data showing superiority of certain CAR T cell products over AHCT in patients with high-risk relapsed or refractory systemic DLBCL or HGBL.…”
Section: Discussionmentioning
confidence: 93%
“…The available evidence suggests that CAR-T cells have good CNS activity. A single-centre retrospective study of seven patients with secondary CNS large cell lymphoma showed promising results with six patients (85%) achieving CR 21. More studies are needed to confirm the durability of remissions.…”
Section: Discussionmentioning
confidence: 99%
“…A small retrospective study also reported CR in 4 of 7 SCNSL patients receiving commercial axicabtagene ciloleucel. (88) Similarly, another series of 8 refractory SCNSL treated with tisagenlecleucel showed a CR rate of 50% with no significant toxicity. (89).…”
Section: Older/unfit Patientsmentioning
confidence: 92%